Plant growth and genetic polymorphism in glyphosate-resistant sourgrass (Digitaria insularis L. Fedde) - Martins, Juliano Francisco [UNESP]; Barroso, Arthur Arrobas Martins [UNESP]; de Carvalho, Leonardo Bianco [UNESP]; Cesarin, Anne Elise [UNESP]; do Amaral, Cárita Liberato [UNESP]; Nepomuceno, Mariluce Pascoina [UNESP]; Desidério, Janete Aparecida [UNESP]; Aguiar, Pedro Luis da Costa Alves [UNESP] (Southern Cross Publishing, 2016)
Weed herbicide resistance has been a challenge in agriculture. The objective of this study was to detect sourgrass (Digitaria insularis (L.) Fedde) glyphosate-resistant plants and to evaluate the growth and polymorphism rate between the resistant and susceptible biotypes, as a subsidy for the integrated management of species. An experiment was conducted primarily for the detection of weed resistance using increasing doses of glyphosate to generate a dose-response curve. Then, an experiment consisting of eight treatments (destructives analysis of growth) and five replications was conducted to characterize and compare the phenological stages of each biotype. In addition to visual assessments, the dry weight and leaf area, absolute and relative growth rates, net assimilation rate and leaf area ratio of plants were determined. Finally, polymorphism among biotypes was determined using inter simple sequence repeat molecular markers. A resistant factor of 3.12 was found among the biotypes. The resistant biotype grew faster and was more robust than the susceptible biotype, arriving first to flowering. The resistant biotype was better adapted to light interception. The 25 inter simple sequence repeat molecular markers analysis showed a polymorphism rate of 56.6% among the analyzed biotypes.
Keywords: Digitaria insularis; Genetic variance; Herbicide resistance; Phenology; Roundup